On consolation and life courage - Kitzmüller, Gabriele; Roxberg, Åsa; Anne Clancy, Anne (Nordisk Tidsskrift for Helseforskning, 2023)
Good interpersonal relationships characterized by an attentive caring presence can help us cope when we are confronted with hardship and suffering. Caring encounters can provide comfort and consolation and give us the courage to carry on despite adversity. Nature can also comfort and empower us, as can other spaces that create a sense of at-homeness and belonging. The phenomenon of comfort has been the subject of inquiry in both philosophy and theology as well as in literature, the visual arts and music. This special issue comprises an introductory text and eight articles written mainly by members of the Research Group Life and Life Courage. The introductory text provides an introduction to the phenomenon of comfort. In the subsequent texts the authors elaborate further on their understanding of the phenomenon from the perspective of health and social care or through a life philosophical lens.